Partial identification of genomic HPPR gene in Orthosiphon aristatus - Mohd Fauzi., Ellya Aqeela (Universiti Malaysia Sarawak (UNIMAS), 2015)
Orthosiphon aristatus (Lamiaceae), locally known as Misai Kucing is a well known medicinal plant which has been used as traditional medicine to treat various human ailments. Many bioactive compound have been identified in medicinal plants which make it beneficial to human health. O. aristatus exhibits high content of secondary metabolites such as rosmarinic acid, a caffeic acid derivative which causes diuretic and therapeutic effects. Hydroxyphenylpyruvate reductase (HPPR) is one of the enzymes that involve in the rosmarinic acid biosynthesis. The focus of this study is to isolate and characterize a genomic HPPR gene from O. aristatus. The isolated HPPR gene was successfully amplified via polymerase chain reaction (PCR). An approximately 2000 bp nucleotide genomic DNA was isolated and further analysed for homology by Blastn. The homology analysis revealed high sequence identity to other plants which contain HPPR gene.